Frequency-controlled electric drive for fan load - Nikulcha, M. V.; Chaikovskyi, T. O. (ТДАТУ, 2021)
Nowadays, it is important to increase the efficiency of the supply of technological machines in the sectors of uninterrupted and high-quality electricity production and to carry out research aimed at creating energy-saving operating regimes. In this respect, particular importance is given to improving the energy efficiency of the production lines and chemical pumping machines with modern electromechanical and semiconductor converters, microprocessing devices for automatic control. Special attention is given to the development of technical means and technologies that ensure energy-saving operating modes of pumping machines by controlled electric drives in chemical industry.
Keywords: extreme electric drive; engine; speed of rotation